The art of a lie : a novel - Shepherd-Robinson, Laura (Atria Books, 2025)
"Following the murder of her husband in what looks like a violent street robbery, Hannah Cole is struggling to keep her head above water. Her confectionary shop on Piccadilly is barely turning a profit, her suppliers conspiring to put her out of business because they don't like women in trade. Henry Fielding, the famous author-turned-magistrate, is threatening to confiscate the money in her husband's bank account because he believes it might have been illicitly acquired. And even those who claim to be Hannah's friends have darker intent. Only William Devereux seems different. A friend of her late husband, Devereux helps Hannah unravel some of the mysteries surrounding his death. He also tells her about an Italian delicacy called iced cream, an innovation she is convinced will transform the fortunes of her shop. But their friendship opens Hannah to speculation and gossip and draws Henry Fielding's attention her way, locking her into a battle of wits more devastating than anything she can imagine..."--